Materials science and technology teachers handbook (Washington, 1994)
This book includes many parts: Introduction to materials science and technology; Creating an MST environment; Standards, learning goals, and assessment; Experiments/Demonstrations;...
Keywords: Khoa học vật liệu,Công nghệ,Materials science,Technology; Dạy và học,Dạy và học,Study and teaching,Study and teaching